2022
DOI: 10.1038/s41420-022-01136-9
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circPOSTN promotes neovascularization by regulating miR-219a-2-3p/STC1 axis and stimulating the secretion of VEGFA in glioblastoma

Abstract: Glioblastoma (GBM), the most malignant type of astrocytic tumor, is one of the deadliest cancers prevalent in adults. Along with tumor growth, patients with GBM generally suffer from extensive cerebral edema and apparent symptoms of intracranial hyper-pressure. Accumulating evidence has demonstrated that circRNA plays a critically important role in tumorigenesis and progression. However, the biological function and the underlying mechanism of circRNA in GBM remain elusive. In this study, by conducting gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…To our best knowledge, hsa-miR-219-2-3p and hsa-miR-218-5p down-regulation in plasma has not been previously reported in the case of HCC. hsa-miR-219-2-3p has been previously shown to be possibly involved in gastric cancerogenesis, the development of pituitary adenomas, and glioblastomas [33‒35]. In addition, functional miRNA studies report the role of hsa-miR-218-5p in the regulation of cell proliferation, metastasis, and invasion in vitro in HCC cell lines [36].…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, hsa-miR-219-2-3p and hsa-miR-218-5p down-regulation in plasma has not been previously reported in the case of HCC. hsa-miR-219-2-3p has been previously shown to be possibly involved in gastric cancerogenesis, the development of pituitary adenomas, and glioblastomas [33‒35]. In addition, functional miRNA studies report the role of hsa-miR-218-5p in the regulation of cell proliferation, metastasis, and invasion in vitro in HCC cell lines [36].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, DSG2 promoted the proliferation and migration of LUAD cell lines and increased the resistance to Osimertinib ( 54 ). In glioblastoma, the cyclic RNA circPOSTN can promote neovascularization by regulating the miR-219a-2-3p/STC1 axis and promoting the expression of VEGFA ( 55 ). Meanwhile, ABCA3 , FRS3 and other genes have also been reported in a variety of cancers ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…CircPOSTN was found to have significantly upregulated levels in GBM tissues and cell lines [ 92 ]. CircPOSTN overexpression was found to facilitate GBM cell proliferation, migration and neovascularization, whereas circPOSTN silencing showed the opposite effects [ 92 ], suggesting a promoting role of circPOSTN in GBM. Further experiments revealed that miR-219a-2-3p was the direct target of circPOSTN and that miR-219a-2-3p could target STC1.…”
Section: Functional Mechanisms Of Circrnas In Gbmmentioning
confidence: 99%
“…Further experiments revealed that miR-219a-2-3p was the direct target of circPOSTN and that miR-219a-2-3p could target STC1. CircPOSTN suppressed miR-219a-2-3p activity and then increased the expression of STC1 [ 92 ], thus promoting tumorigenesis. Moreover, circPOSTN was revealed to facilitate GBM neovascularization by inducing VEGFA secretion.…”
Section: Functional Mechanisms Of Circrnas In Gbmmentioning
confidence: 99%
See 1 more Smart Citation